Iguanas for Dummies - Kaplan, Melissa (Hoboken, N. J. John Wiley & Sons, Inc., 2000)
Advises how to select and care for an iguana, providing tips on health, socialization, habitat, and other issues.
Include Illustrations, Appendices and Index.
Keywords: Iguanas as pets